Teacher Professionalism and Principal Supervision's Impact on Teacher Performance - Agustina, Yuli; Saxena, Rachana (PPSDP International Journal of Education, 2022)
The purpose of this study is to see if there is an influence of teacher professionalism and principle supervision on teacher performance. This study is an ex post facto quantitative study using a questionnaire instrument. The respondents in this study were 31 teachers from SMA Negeri 2 Kayuagung. The data were analyzed using the SPSS application, which calculated regression, t-tests, and F-tests. The study's findings revealed that teacher professionalism and principle supervision had a substantial influence on teacher performance. Previous researchers have never conducted a study like this previously since prior studies only focused on characteristics of teacher professionalism and organizational environment on teacher performance and components of teacher professionalism and teaching experience on teacher performance. While the purpose of this study is to investigate the relationship between professionalism and supervision and high school performance. This study is anticipated to help school principals enhance performance by boosting teacher professionalism and providing adequate monitoring.